2010
DOI: 10.2527/jas.2009-2538
|View full text |Cite
|
Sign up to set email alerts
|

Response to selection for bacterial cold water disease resistance in rainbow trout1,2

Abstract: A family-based selection program was initiated at the National Center for Cool and Cold Water Aquaculture in 2005 to improve resistance to bacterial cold water disease (BCWD) in rainbow trout. The objective of this study was to estimate response to 2 generations of selection. A total of 14,841 juvenile fish (BW = 3.1 g; SD = 1.1 g) from 230 full-sib families and 3 randomly mated control lines were challenged intraperitoneally with Flavobacterium psychrophilum, the bacterium that causes BCWD, and mortalities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 45 publications
7
105
0
Order By: Relevance
“…Therefore, challenge tests will often be more accurate and reliable than field outbreaks, due to decreased environmental variability and higher practical feasibility. In fact, challenge testing is currently used to select for resistance to viral, bacterial, and parasitic diseases in breeding programs for Atlantic salmon and rainbow trout (Gjøen and Bentsen, 1997; Leeds et al, 2010; Yáñez and Martínez, 2010; Ødegård et al, 2011; Gjedrem, 2012; Wiens et al, 2013a). …”
Section: Conventional Breeding For Disease Resistance In Salmonidsmentioning
confidence: 99%
“…Therefore, challenge tests will often be more accurate and reliable than field outbreaks, due to decreased environmental variability and higher practical feasibility. In fact, challenge testing is currently used to select for resistance to viral, bacterial, and parasitic diseases in breeding programs for Atlantic salmon and rainbow trout (Gjøen and Bentsen, 1997; Leeds et al, 2010; Yáñez and Martínez, 2010; Ødegård et al, 2011; Gjedrem, 2012; Wiens et al, 2013a). …”
Section: Conventional Breeding For Disease Resistance In Salmonidsmentioning
confidence: 99%
“…Henryon et al (2002) found resistance to viral hemorrhagic septicemia (VHS) to be low-to-moderately heritable (h 2 =0.14) when resistance was assessed as a longitudinal trait, whereas Dorson et al (1995) reported resistance to VHS to be highly heritable (h 2 =0.63) when resistance was assessed as a percentage on the angular scale. Recently, heritability estimate of 0.23 was found from linear animal model in rainbow trout for survival against bacterial cold water disease (Leeds et al 2010). However, the heritability for time to death from edwardsiellosis was found to be moderate (0.22 ± 0.07) in rohu families.…”
Section: Discussionmentioning
confidence: 98%
“…time until death following challenge (Henryon et al 2005). Various workers have found encouraging results for selection for resistance to several bacterial diseases in different fish such as the following 1) furunculosis in Atlantic salmon and common carp (Sovenyi et al 1988;Gjedrem et al 1991;Marsden et al 1996); 2) bacterial kidney disease and cold water vibriosis in Atlantic salmon (Gjedrem and Gjoen 1995); 3) Aeromonas hydrophila infection in Nile tilapia and rohu (Sarder et al 2001;Sahoo et al 2004;Mahapatra et al 2008); 4) enteric red mouth disease and rainbow trout fry syndrome in rainbow trout (Henryon et al 2005); and 5) bacterial cold water disease in rainbow trout (Silverstein et al 2009;Leeds et al 2010). In our preliminary study, a wide variation in survival against Edwardsiella tarda infection in fullsib families of rohu was also noted .…”
Section: Introductionmentioning
confidence: 97%
“…Disease resistance can be improved through selective breeding (3, 4), and recent farm trials of a selectively bred line (ARS-Fp-R) demonstrated significantly higher survival at locations where BCWD is endemic (5, 6). Flavobacterium psychrophilum is the causative agent of BCWD and a reference genome sequence is available (7).…”
Section: Genome Announcementmentioning
confidence: 99%